Studi Eksperimental Angka Setana Diproduksi dari Minyak Goreng Bekas - Chairul Fahmi, Muhamamad; Idris, Muhammad (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Biodiesel is a potential alternative to replace diesel due to its renewable and environmentally friendly raw materials. Used cooking oil can be utilized as a feedstock for biodiesel; however, the high free fatty acid content requires pretreatment with esterification before transesterification. This study aims to determine the effect of reaction time variation (60, 70, 80, 90, 100 minutes) on the cetane number of biodiesel produced at 60°C and a speed of 1050 rpm. The esterification and transesterification processes use 0.5% NaOH catalyst and methanol in a 1:2 ratio, mixed with used cooking oil. After transesterification, the mixture is settled for 20 minutes, then the biodiesel is separated and washed with distilled water at 50°C and evaporated at 90-100°C. The cetane number test results are as follows: 60 minutes (44.54), 70 minutes (44.54), 80 minutes (44.54), 90 minutes (44.47), and 100 minutes (44.60). This study shows that the cetane number of the produced biodiesel does not meet the biodiesel quality standards and is not yet suitable for use by the Ministry of Energy and Mineral Resources (ESDM).